2016
DOI: 10.15244/pjoes/61628
|View full text |Cite
|
Sign up to set email alerts
|

How 23-year Continuous Soybean Cultivation Led to More SOC and Thermal Energy Stored in Mollisol Micro-Aggregates

Abstract: Aggregate has been recognized as a key element in the stabilization of soil organic carbon (SOC). Several researchers have done outstanding work on identifying and isolating aggregates and their physiochemical properties. However, thermal stability of SOC in soil aggregates has not yet been adequately explored. The main objective of the study was to clarify the protection of aggregation on SOC from thermal characters, and provide evidence on whether thermal analysis could be a potential rapid method to determi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…Qiao et al [33] suggested that micro-aggregates played key roles in protecting SOC based on more recalcitrant SOC stored in micro-aggregates. However, higher organic carbon content in the macroaggregates (> 2 mm fraction) compared to the micro-aggregates ( 0.2 mm fraction) in our results, that was similar to previous studies [19], which observed that when organic inputs were increased in a calcareous soil, a greater proportion of stable macro-aggregate (> 250um) would be formed in comparison to a non-calcareous soil of similar characteristics.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Qiao et al [33] suggested that micro-aggregates played key roles in protecting SOC based on more recalcitrant SOC stored in micro-aggregates. However, higher organic carbon content in the macroaggregates (> 2 mm fraction) compared to the micro-aggregates ( 0.2 mm fraction) in our results, that was similar to previous studies [19], which observed that when organic inputs were increased in a calcareous soil, a greater proportion of stable macro-aggregate (> 250um) would be formed in comparison to a non-calcareous soil of similar characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…Mean weight diameter (MWD) of water stable aggregates has been recognized as an important indicator on the capability of the soil to resist against water erosional forces. Meanwhile, stable aggregate played an important role in the stabilization of SOC [33]. Micro-aggregates are bound together by young organic matter into larger macro-aggregates and a breakdown of macro-aggregates results in a release of labile SOM [4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…4.4Aggregate-SOM content increased with increasing aggregate size Qiao et al(2016) suggested that micro-aggregates played key roles in protecting SOC based on more recalcitrant SOC stored in micro-aggregates. However, higher organic carbon content in the macro-aggregates (>2mm fraction) compared to the micro-aggregates (<0.2 mm fraction) in our results, that was similar to previous studies (Fernandez-Ugalde et al,2011), which observed that when organic inputs were increased in a calcareous soil, a greater proportion of stable macro-aggregate (>250um) would be formed in comparison to a non-calcareous soil of similar characteristics.…”
Section: Aggregate-caco 3 Content Decreased With Increasing Aggregate Sizementioning
confidence: 96%
“…It was believed that the SOC content played an important role in the soil aggregation (Nie et al, 2017). Meanwhile, stable aggregate played an important role in the stabilization of SOC (Qiao et al, 2016). It is generally accepted that the stability of SOC in soil aggregates due to the protection of aggregate structure from microbial decomposition (Qiao et al, 2016).…”
Section: Introductionmentioning
confidence: 99%